Small RAB GTPases Regulate Multiple Steps of Mitosis - Miserey-Lenkei, Stéphanie; Colombo, María I. (Frontiers in Cell and Developmental Biology, 2016)
GTPases of the RAB family are key regulators of multiple steps of membrane trafficking. Several members of RAB GTPases family have been implicated in mitotic progression. In this review, we will first focus on the function of endosomes-associated RABs GTPases reported in early steps of mitosis, spindle pole maturation and mainly during cytokinesis. Second, we will expose the role of Golgi-associated RAB GTPases at the metaphase/anaphase transition and during cytokinesis.